Design and Development of a Web-Based Medical Record Retention Information System at Polyclinic X Jember Regency - Farlinda, Sustin; Nurjannah, Nada Savira; Yunus, Muhammad; Pratama, Mudafiq Riyan (International Journal of Health and Information System, 2023)
Medical record retention activities that have been carried out at Polyclinic X Jember Regency have encountered obstacles in sorting files that are still manual, starting with the officer checking the month and year of the patient's last visit to the Polyclinic's SIM Clinic, then taking several medical records on the storage rack and recording the medical record number for sorting. There are quite a lot of files on the storage rack, making officers have to sort the files one by one. The type of research used R&D with the Waterfall system development method, namely Requirement Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, also Operation and Maintenance. Data collection techniques using interviews and observations with 2 respondents, namely the head of polyclinic and medical records officers. This study aims to design and create a web-based medical record retention information system by minimizing errors in sorting medical record files and facilitating the performance of medical record officers in the filing section. The result of this research is a web-based medical record retention information system created using the PHP programming language.